(untitled) (Scientific journal of the Fergana State University, 2024)
In the Fergana Valley, a study was conducted to study and analyze the distribution, biology and ecology of species belonging to the genus Sitona Germar, 1817. Researches were conducted in a number of regions of Andijan, Fergana and Namangan regions of the Fergana Valley, in various agrobiocenoses. Determining the number of long-nosed beetles and collecting their samples was carried out on the basis of the route-monitoring method, starting from March, every 5-7 days during the vegetation of plants, and 3 times a month on routes, in areas where pest control was not carried out. As a result of research, Sitona callosus Gyllenhal, 1834, Sitona crinitus Herbst, 1795., Sitona cylindricollis Fåhraeus, 1840., Sitona flavescens Fabricius, 1787., Sitona humeralis Steph Sitona inops Gyllenhal, 1832., Sitona lineellus Bonsdorff, 1785., Sitona longulus Gyllenhal, 1834., Sitona sulcifrons Thunberg, 1798 distribution was recorded and bioecology was studied.